Are vulnerable communities digitally left behind in social responses to natural disasters? An evidence from Hurricane Sandy with Twitter data. (July 2019) - Wang, Zheye; Lam, Nina S.N.; Obradovich, Nick; Ye, Xinyue
Abstract: Social media data is increasingly being used to improve disaster resilience and response. Recent years have seen more efforts to integrate social media feeds with various demographic and socioeconomic variables to gain insight into the geographical and social disparities in social media use surrounding disasters. However, vulnerability concepts and indicators have been largely overlooked despite that they can offer aid in understanding and measuring the communities' sensitivity to natural hazards and their capability of responding to and recovering from disasters. This study addresses a research question: Are vulnerable communities digitally left behind in social responses to natural disasters? Our empirical analysis is based on Hurricane Sandy and is conducted in a pre-disaster setting with spatial regression modeling. We observe that physically vulnerable communities had more intense social responses while socially vulnerable communities were digitally left behind in pre-disaster social responses to Hurricane Sandy. Highlights: Twitter activities were used to measure social responses to Hurricane Sandy. The relationship between vulnerability and online social responses to Hurricane Sandy was examined Empirical analysis was conducted in a pre-disaster setting with spatial regression modeling. Physically vulnerable communities had more intense social responses. Socially vulnerable communities were digitally left behind.